Proposals for a revised laboratory school for the College of Education Thailand - Pairoh Tandikul 1913- (1967)
This study aimed to analyze the trends in the organization, administration, and supervision of laboratory schools in the Philippines, and to develop from such an analysis, principles common to all laboratory schools for the College of Education. Data were gathered through interview of the principal and acting assistant principal of the UP Elementary School, and direct ovservation of the actual pratice of organization, administration, and supervision of the school. It was proposed that the laboratory school in Prasarn Mit, Bangkok should have a philoshophy guided by the significance of the child in the selection of the subject matter to be taught. It should also operate democratically in its organization, administration, and supervision. Qualified non-teaching staff and highly qualified and experienced teachers are much needed.
"April 1967."
Vita.
Thesis (M. Education)--University of the Philippines, Diliman.
Keywords: Laboratory schools -- Philippines; Teachers -- Training of -- Thailand